2012
DOI: 10.1007/978-3-642-34327-8_33
|View full text |Cite
|
Sign up to set email alerts
|

A Reuse-Oriented Development Process for Component-Based Robotic Systems

Abstract: Abstract. State of the art in robot software development mostly relies on class library reuse and only to a limited extent to component-based design. In the BRICS project we have defined a software development process that is based on the two most recent and promising approaches to software reuse, i.e. Software Product Line (SPL) and Model-Driven Engineering (MDE). The aim of this paper is to illustrate the whole software development process that we have defined for developing flexible and reusable component-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…The design of a robotic system for robust navigation involves coordination of different tasks, such as path planning, motion control, and sensor data processing. Brugalli et al [5] investigated several development environments to identify existing modules associated with the design of robust navigation functionalities. They realized that modules related to robust navigation typically refer to the same tasks of robotics, but different names are used.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The design of a robotic system for robust navigation involves coordination of different tasks, such as path planning, motion control, and sensor data processing. Brugalli et al [5] investigated several development environments to identify existing modules associated with the design of robust navigation functionalities. They realized that modules related to robust navigation typically refer to the same tasks of robotics, but different names are used.…”
Section: Case Studymentioning
confidence: 99%
“…Currently, the services identified for robust navigation are strongly dependent on MoveBase to start and, therefore, to work properly. However, a study has already demonstrated these services can work independently after a refactoring process [5].…”
Section: Case Studymentioning
confidence: 99%
“…Recently, a reuse-oriented development process for component-based robotic systems [18] was published following the developed design philosophy using the BRICS Integrated Development Environment (BRIDE) [17], which is a prototypical software tool chain. It includes a graphical user interface to support their approach for robotic system engineering.…”
Section: Related Workmentioning
confidence: 99%
“…The final report summarizes the requirements for control systems as: generality, in order to support the largest number of mobile robotics scenarios; open source philosophy, as it allows easy reuse and debug of applications and comparative experiments of different approaches; layered application layout, to organize and encapsulate methods and information, allowing the developer to focus only on the needed part of the system; heterogeneous systems support, for it improves the capabilities of the complete system, as a team of different robots can, in some situations, be more effective in a given task; real-time reconfiguration, in order to add some fault tolerance and flexibility to the system. Besides these topics, the requirements of quality, functionality and procedure are proposed by Brugali [19], [20], [21]. Functionality is the concept of the need for the system's features.…”
Section: Related Workmentioning
confidence: 99%